The Pasha How Mehemet Ali defied the West ; 1839 - 1841 - Ufford, Letitia Wheeler (McFarland, 2007)
"In 1811, Mehemet Ali Pasha, governor of Egypt, gained control of that country by a massacre of the Mamluks. This book shines a light on the great international crisis of 1839-1841, precipitated by the Pasha when his army threatened to shatter the Ottoman Empire, tempting the European Powers to fight each other over control of the pieces"--Provided by publisher.